Five-year follow-up results of aerobic and impact training on bone mineral density in early breast cancer patients - L. Vehmanen; H. Sievänen; P. Kellokumpu-Lehtinen; R. Nikander; R. Huovinen; J. Ruohola; H.M. Penttinen; M. Utriainen; K. Tokola; C. Blomqvist; T. Saarto (SPRINGER LONDON LTD, 2022)
A 12-month exercise program reversibly prevented hip bone loss in premenopausal women with early breast cancer. The bone-protective effect was maintained for 2 years after the end of the program but was lost thereafter. Purpose Breast cancer survivors are at an increased risk for osteoporosis and fracture. This 5-year follow-up of a randomized impact exercise intervention trial evaluated the maintenance of training effects on bone among breast cancer patients. Methods Five hundred seventy-three early breast cancer patients aged 35-68 years and treated with adjuvant therapy were allocated into a 12-month exercise program or a control group. Four hundred forty-four patients (77%) were included in the 5-year analysis. The exercise intervention comprised weekly supervised step aerobics, circuit exercises, and home training. Areal bone mineral density (aBMD) was measured by dual-energy X-ray absorptiometry. Physical activity was estimated in metabolic equivalent (MET) hours per week and physical performance assessed by 2-km walking and figure-8 running tests. Results In premenopausal patients, the 12-month exercise program maintained femoral neck (FN) and total hip (TH) aBMD for 3 years, but the protective effect was lost thereafter. The mean FN aBMD change in the exercise and control groups was - 0.2% and - 1.5% 1 year, - 1.1% and - 2.1% 3 years and - 3.3% versus - 2.4% 5 years after the beginning of the intervention, respectively. Lumbar spine (LS) bone loss was not prevented in premenopausal women and no training effects on aBMD were seen in postmenopausal women. The main confounding element of the study was the unexpected rise in physical activity among patients in the control group. The physical performance improved among premenopausal women in the exercise group compared with the controls. Conclusion The 12-month exercise program prevented FN and TH bone loss in premenopausal breast cancer patients for 3 years. The bone-protective effect was reversible and lost thereafter.